The house of last resort : a novel [large type] - Golden, Christopher (Thorndike Press large print high octane, 2024)
"Across Italy there are many half-empty towns, nearly abandoned by those who migrate to the coast or to cities. The beautiful, crumbling hilltop town of Becchina is among them, but its mayor has taken drastic measures to rebuild--selling abandoned homes to anyone in the world for a single Euro, as long as the buyer promises to live there for at least five years. It's a no-brainer for American couple Tommy and Kate Puglisi. Both work remotely, and Becchina is the home of Tommy's grandparents, his closest living relatives. It feels like a romantic adventure, an opportunity the young couple would be crazy not to seize. But from the moment they move in, they both feel a shadow has fallen on them. Tommy's grandmother is furious, even a little frightened, when she realizes which house they've bought. There are rooms in an annex at the back of the house that they didn't know were there. The place makes strange noises at night, locked doors are suddenly open, and when they go to a family gathering, they're certain people are whispering about them, and about their house, which one neighbor refers to as The House of Last Resort. Soon, they learn that the home was owned for generations by the Church, but the real secret, and the true dread, is unlocked when they finally learn what the priests were doing in this house for all those long years...and how many people died in the strange chapel inside. While down in the catacombs beneath Becchina...something stirs"--